Comparison of knowledge on asthma: doctors completing internal medicine residency and doctors completing medical school - Vieira, Joaquim Edson (2001)
CONTEXT: Asthma has been reported as a disease of increasing prevalence. OBJECTIVE: To assess the level of information and knowledge about asthma by means of a questionnaire among recent graduate physicians applying for medical residency at the Clinical Hospital of the University of São Paulo Medical School, Brazil. DESIGN: 14 multiple-choice questions for asthma diagnosis and management. SETTING: University of São Paulo Medical School (FMUSP). PARTICIPANTS: Recent graduate physicians applying for the medical residency program at FMUSP in 1999 (n = 448) and physicians that had completed 2 year of internal medicine residency (n = 92). MAIN MEASUREMENTS: We applied a questionnaire with 14 multiple-choice questions about the management of asthma based upon the Expert Panel Report 2 – Guidelines for the Diagnosis and Management of Asthma, NIH/NHLBI, 1997 (EPR-2). RESULTS: The medical residency program in Internal Medicine improved treatment skills (the ability to propose adequate therapy) when compared to medical education (a score of 57.2% versus 46.9%, P < 0.001) but not diagnosis knowledge (understanding of asthma symptoms related to medicine intake) (33.5% versus 33.3%, P = 0.94). Treatment skills were higher among physicians who received their Medical Degree (MD) from public-sponsored medical schools in comparison with those from private schools [49.7 (SE 1.17)] versus [41.8 (SE 1.63)], P < 0.001. CONCLUSION: Medical schools might consider reevaluating their programs regarding asthma in order to improve medical assistance, especially when considering the general results for residents, as they were supposed to have achieved performance after completing this in-service training.